Pan-labral tear of the shoulder joint in a non-athlete patient with six years history of recurrent shoulder subluxations and intraoperative findings of osteoarthritic changes: A case report. (April 2020) - Maalouly, Joseph; Aouad, Dany; Tawk, Antonios; Dib, Nabil; El Rassi, Georges
Abstract: The hypermobility of the glenohumeral joint accounts for its anatomic predisposition for instability and dislocation. The stability of the shoulder joint is dependent on static and dynamic soft tissue structures, among which is the labrum. Circumferential labral tears are a rare pathological entity of shoulder instability that have not been commonly reported in the literature. A detailed history and physical examination are crucial for accurate diagnosis since MRIs have a poor sensitivity. A 40-year-old male patient with a history of atraumatic recurrent left shoulder subluxations for 6 years. On physical examination, there was no evidence of motor or sensory deficit. MR images were suggestive of Hills-Sachs lesion with intact rotator cuffs. Pan-labral tear repair via arthroscopy presents a unique challenge, even for the skilled orthopedic surgeon. Hence, the repair demands accessory portals and percutaneous techniques for the adequate placement of anchors. The purpose of this case is the rare presentation of a pan-labral tear repaired arthroscopically.